CHIP-mediated CIB1 ubiquitination regulated epithelial–mesenchymal transition and tumor metastasis in lung adenocarcinoma - Liu, Yuanqi (Cell Death Differ, 2020)
CIB1 is a homolog of calmodulin that regulates cell adhesion, migration, and differentiation. It has been considered as an oncogene in many tumor cells; however, its role in lung adenocarcinoma (LAC) has not been studied. In this study, the expression levels of CIB1 in LAC tissues and adjacent normal tissues were examined by immunohistochemistry, and the relationship between CIB1 expression and patient clinicopathological characteristics was analyzed. The effects of CIB1 on epithelial–mesenchymal transition (EMT), migration, and metastasis of LAC cells were determined in vitro and vivo. Proteins interacting with CIB1 were identified using electrospray mass spectrometry (LS-MS), and CHIP was selected in the following assays. Carboxyl-terminus of Hsp70-interacting protein (CHIP) is a ubiquitin E3 ligase. We show that CHIP can degrade CIB1 via promoting polyubiquitination of CIB1 and its subsequent proteasomal degradation. Besides, lysine residue 10 and 65 of CIB1 is the ubiquitinated site of CIB1. Furthermore, CHIP-mediated CIB1 downregulation is critical for the suppression of metastasis and migration of LAC. These results indicated that CHIP-mediated CIB1 ubiquitination could regulate epithelial–mesenchymal and tumor metastasis in LAC.